2002
DOI: 10.2224/sbp.2002.30.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gender and Education on the Moral Reasoning of Kuwait University Students

Abstract: The moral reasoning of 189 undergraduate students from the College of Education, Kuwait University was studied, using the Defining Issues Test (DIT) by Rest (1990). The subjects ranged in age from 18 to 26 years (mean age =20.83). The results revealed that the sample reasoned predominantly at stage 4. Principled Morality Percentage Score (P%-score) was found to be below the norms reported in the literature for this group. There were no gender differences in moral reasoning. However, formal education did have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 19 publications
1
15
0
3
Order By: Relevance
“…For replicability, former Muslim studies of Kohlbergian moral reasoning provide rather clear evidence of cross-study consistency and test-retest reliability (Al-Ansari, 2002;Bouhmama, 1988). These studies showed that Muslims tend to reason predominantly at the conventional stages of moral development and to range in their P score standard deviation from 10 to 20 points, a range similar to the ones documented from various Western samples.…”
Section: Dependent Variablementioning
confidence: 70%
“…For replicability, former Muslim studies of Kohlbergian moral reasoning provide rather clear evidence of cross-study consistency and test-retest reliability (Al-Ansari, 2002;Bouhmama, 1988). These studies showed that Muslims tend to reason predominantly at the conventional stages of moral development and to range in their P score standard deviation from 10 to 20 points, a range similar to the ones documented from various Western samples.…”
Section: Dependent Variablementioning
confidence: 70%
“…This interactive learning describes the context of a historical phenomenon that never existed. Through interactive analytic methods descriptive, with a variation of a case study, learning "role playing" information very effectively in the effort to inculcate the values of character education in the nation's history in school subjects [44], [45].…”
Section: Advances In Social Science Education and Humanities Researcmentioning
confidence: 99%
“…Baek has concluded that Kohlberg's framework alone is insufficient to explain Korean children's moral reasoning. In another study, Al-Ansari (2002) reported that Kuwaiti university students reason predominantly at the conventional level. Al-Ansari suggested that "adherents to the Muslim religion rely more on divine law for moral decision-making than on justice as measured within the Kohlbergian framework" (p. 79).…”
mentioning
confidence: 96%
“…Since cross-cultural differences in moral orientation is still a controversial issue for some researchers (e.g., Al-Ansari, 2002;Baek, 2002), further research is needed to examine whether people in individualistic societies are oriented toward universal moral principles, including justice and rights, to a larger extent than people in collectivistic societies.…”
mentioning
confidence: 99%